A macro-element model for predicting the combined load behaviour of spudcan foundations in clay overlying sand. Issue 12 (27th September 2021) - Wang, Yifa; Cassidy, Mark J.; Bienen, Britta
Abstract : A macro-element model for predicting the load-displacement behaviour of a spudcan foundation in clay overlying sand when subjected to combined vertical, horizontal, and moment loading is introduced. Observations from detailed drum centrifuge tests that measured the effect of the underlying sand layer on the foundation behaviour are combined with finite-element results and theoretical developments to derive the components of the model. The yield surface defined by the centrifuge test results suggests that as the spudcan nears the underlying sand layer, the absolute horizontal capacity remains relatively constant, while the vertical and moment capacities increase at approximately the same normalised rate. The model is demonstrated to accurately predict foundation behaviour by retrospectively simulating the experimental results. This macro-element model has the advantage that it can be integrated into the structural analyses of jack-up platforms required for site-specific assessments.